APPLICATION OF THE TEAM GAMES TOURNAMENT (TGT) TYPE COOPERATIVE LEARNING MODEL IN THE SUBJECT OF ECONOMICS, MONEY SUPPLY SUB-MATERIAL, CLASS XI IPS AT YOUR CATHOLIC HIGH SCHOOL, LURI - WAINGAPU - Florida Dapa (Arthaniti Studies, 2024)
This research aims to determine the application of appropriate learning models in improving learning competence and raising student motivation in Economics Subjects at Anda Luri Catholic High School, Waingapu when carrying out Field Experience Practices (PPL) in fulfilling a series of Teacher Professional Development Programs (PPG) through the System. in the Network (Online). This research is included in qualitative descriptive research with a case study approach. The research subjects were 32 students in class IX of Anda Luri Catholic High School who experienced problems in learning based on the teacher center method. This data collection was carried out in a combined manner, qualitative data analysis, drawing conclusions and verification. Based on the research results, it was found that the lack of student motivation to learn was caused by students being bored following the learning that teachers often do using the lecture method. Apart from lectures, the method that teachers always use is assignments. Some students admit that they are bored with assignments that are only theoretical. Just copy from the textbook